2020
DOI: 10.1002/adhm.202000174
|View full text |Cite
|
Sign up to set email alerts
|

Bench‐to‐Bedside Lessons Learned: Commercialization of an Acellular Nerve Graft

Abstract: Peripheral nerve injury can result in debilitating outcomes including loss of function and neuropathic pain. Although nerve repair research and therapeutic development are widely studied, translation of these ideas into clinical interventions has not occurred at the same rate. At the turn of this century, approaches to peripheral nerve repair have included microsurgical techniques, hollow conduits, and autologous nerve grafts. These methods provide satisfactory results; however, they possess numerous limitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 136 publications
0
29
0
Order By: Relevance
“…Currently, two decellularised human nerve grafts have undergone multicentre clinical evaluations; a non-commercial nerve graft for sensory nerve defects in China ( He et al, 2015 ) and the commercial Avance ® nerve graft from Axogen in the United States ( Kasper et al, 2020 ; Safa et al, 2020 ). Both are sterilised with 25 kGy gamma radiation; however, it is unclear why this method was selected, and limited data are available regarding the effects of the sterilisation process in isolation on the properties of the decellularised nerve tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, two decellularised human nerve grafts have undergone multicentre clinical evaluations; a non-commercial nerve graft for sensory nerve defects in China ( He et al, 2015 ) and the commercial Avance ® nerve graft from Axogen in the United States ( Kasper et al, 2020 ; Safa et al, 2020 ). Both are sterilised with 25 kGy gamma radiation; however, it is unclear why this method was selected, and limited data are available regarding the effects of the sterilisation process in isolation on the properties of the decellularised nerve tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Both are sterilised with 25 kGy gamma radiation; however, it is unclear why this method was selected, and limited data are available regarding the effects of the sterilisation process in isolation on the properties of the decellularised nerve tissue. The results of initial trials indicated that both grafts were safe, did not elicit an adverse host immune response, and revealed that (at least partial) functional restoration could be achieved in short to moderate length (0.5–5 cm) defects ( He et al, 2015 ; Kasper et al, 2020 ; Safa et al, 2020 ). These initial data suggest that sterilisation with ionising radiation does not impair functional properties of decellularised nerves.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14–16 ] Multiple physical cues were also introduced into same nerve guidance graft systems to achieve improved outcomes and functional recovery. [ 17–19 ] Although recent studies using some of these approaches have revealed significant improvements in axonal regeneration and peripheral nerve repair, [ 3,13,20 ] challenges remain to optimize these physical factors.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral nerve axons can spontaneously regenerate to a certain extent after injury, but the probability of recovery decreases as the level of injury increases. Current therapeutic procedures are surgical, employing biomaterials to bridge nerve defects with varying degrees of success [24][25][26]. To enhance the probability of successful outcomes, the use of pharmacological agents and biomolecules, such as microRNAs or growth factors to promote nerve regeneration have gained attention over the last few years [27][28][29].…”
Section: Introductionmentioning
confidence: 99%